Measuring the impact of practicum schedule and mental workload on stress levels in hybrid learning: A case study in Physics practicum - Ani Umyati; Selli Yanasari; Nuraida Wahyuni; Ade Sri Mariawati (Journal Industrial Servicess, 2022)
The Physics Laboratory of the Faculty of Engineering, University of Sultan Ageng Tirtayasa, has implemented hybrid learning-based learning after the Covid-19 pandemic abated. Students admitted to online practicum the previous semester said they felt depressed and overthinking while participating in the physics practicum. The assignments and report must be handwritten after they watch a video explanation of the experimental procedure. The internet network condition is also an obstacle for online practicum. Based on these problems, examining the impact of hybrid learning-based learning in shift practicum and mental workload on stress levels was necessary. This study aims to identify the mental workload experienced by online and offline participants in the Physics Laboratory practicum. The advantage of this study is to review two practicum methods, online and offline practicum. The research instruments used to measure the mental workload and stress level experienced by students are NASA-TLX and DASS-21, respectively. The results showed a simultaneous influence between shift practicum and mental workload on stress levels. The mental workload on the stress level of online and offline practice is significantly different. However, the shift of practicum to the stress level of online and offline practice is similar—the mental workload of online and offline practice in the dominant medium and heavy categories. Heavy and normal categories dominate stress levels. The dominant mental workload factors are effort, frustration, and physical demand.